PENDAMPINGAN MASYARAKAT DALAM PEMANFAATAN LIMBAH BATOK KELAPA MENJADI PRODUK BRIKET SEBAGAI ALTERNATIF BAHAN BAKAR RAMAH LINGKUNGAN DI DESA SELONG BELANAK - Putri, Aprila Anjani; Listiawati, Nadya; Sallahuddin, Imam Soleh; Putri, Deffi Cantika; Lestari, Febbyola Tri; Cupydo, Cussiana; Wulandari, Wiwik; Vanita, Baiq Enjie Putri; Azzahro, Adistya Revolista; Kadnezar, Ahmad Ariel; Maulana, Aldian; Supryadi, Didy Ika (Universitas Mataram, 2025)
This community service program was carried out in Selong Belanak Village, Praya Barat District, Central Lombok Regency, with the aim of improving the knowledge and skills of the local community in utilizing coconut shell waste into eco-friendly briquettes. The implementation method consisted of three stages: collecting coconut shells, processing them into briquettes, and conducting socialization and demonstrations. The results showed that although the initial stages of collection and production were carried out by the KKN students, the community became actively involved during the socialization stage. Several technical challenges were encountered, such as limited raw materials, weather constraints, lack of equipment, and difficulties in determining the right adhesive composition. However, through continuous improvements, the students successfully produced higher-quality briquettes that were denser and more durable. The socialization activity involving the Puncak Gili Lawang Sejahtera Group was attended by 15 participants and succeeded in increasing community awareness of the benefits of briquettes as an alternative energy source. Thus, this program has achieved its objectives by reducing environmental pollution, enhancing community skills, and opening new business opportunities based on local potential.